The public domain song anthology : with modern and traditional harmonization - Berger, David; Israels, Chuck (Charlottesville, Virginia : Aperio Press, 2020)
A collection of 348 popular songs with modern and traditional harmonization for both study and performance. This open educational resource was curated by two leading jazz repertory experts and consists of songs in the US public domain. This anthology is the first of its kind and is free for students and performers to use, adapt, remix, and share. The songs, many of which are at risk of being forgotten, are free of copyright restrictions and are available in multiple formats to promote greater usage and dissemination.
"Popular music for study and performance"--Title page
Keywords: Popular music; Jazz; Blues (Music); Spirituals (Songs); Electronic books